A Randomised Trial of Subcutaneous Low Molecular Weight Heparin (CY 216) Compared with lntravenous Unfractionated Heparin in the Treatment of Deep Vein Thrombosis - A Collaborative European Multicentre Study; Ninet, J; Bachet, Ph; Prandoni, P; Ruol, A; Vigo, M; Barret, A; Mericq, O; Boneu, B; Janvier, G; Duroux, P; Girard, Ph; Laprevote-Heully, M C; Sourou, P; Robert, D; Chagny, M; Nenci, G; Agnelli, G; d’Addato, M; Palumbo, H; Bensaid, J; Gouffault, J; Leborgne, P; Hellocco, A Le; Ducreux, J C; Tempelhoff, G; Sala-Planell, E; Rosendo-Carrera, A; Torres-Gomez, A; Blettery, B; Bachmann, F; Gaux, J C; Muntlak, H; Caulin, Ch; Bergmann, J F (Thrombosis and Haemostasis, 1991)
The standard treatment of deep vein thrombosis is given by continuous intravenous infusion of unfractionated heparin. This entails hospitalisation, nursing care, immobility and repeated laboratory tests (e.g. activated partial thromboplastin time [APTT], platelet count). In addition approximately 10% of patients suffer major haemorrhages. The potential advantages of a low molecular weight heparin (CY 216) given subcutaneously were explored in a randomised trial with blind quantitative evaluation of venograms. The study included 166 patients and both “therapeutic efficacy” and “intention to-treat” analyses showed that subcutaneous CY 216 in fixed doses based only on body weight was more effective on the Arnesen and Marder phlebographic scores than continuous i. v. standard heparin with daily dose adjustment according to results of coagulation tests. There was no increase in the risks of pulmonary embolism, haemorrhage or clot extension.